El complejo Sogata y el virus de la hoja blanca, en el cultivo de arroz en Colombia - Cuevas Medina, Alfredo; Espinosa, John Jairo; Pérez, Cristo Rafael (Gabriel Robayo Vanoy, 2018)
Arroz-Oryza sativa